Effects of melatonin on liver of rats with experimental hyperthyroid - Öner, J; Ozan, E (Sciendo, 2005)
The aim of this study was to investigate the structural changes that occurred in the liver of rats with experimental hyperthyroidism and the possible effects of melatonin on these changes. The animals were designated as control group (group 1), 3,3', 5Triiodo-(L)-Thyronine (T-3) injected group (group II) and T-3+ melatonin injected group (group III). At the end of study, tissue specimens were examined for changes in structure. In the T3 injected group, dilatation in sinusoids and pale cytoplasm were observed, as well as an increased number of the Kupffer cells and an increased amount of glycogen. In T3 melatonin injected group, the amount of glycogen was similar to the T-3+ injected groups while the number of Kupffer cells increased but sinusoid largeness and hepatocyte structure were similar to the control. On electron microscopic examination the mitochondria of T-3 injected group were slightly larger than those of the control group. In T-3+ melatonin injected group enlargement in the spaces of Disse, increased number of lipid vacuoles of Ito cells and increased number of microvilli of hepatocytes were observed. Kupffer cells were more active in this group. The results of this study indicate that T-3 injection causes structural changes in the liver, and melatonin hormone has a small, if any, protective effect on the liver of rats with hyperthyroid.
Keywords: hyperthyroidism; liver; melatonin; rat